Contemporary Management of Axillo-subclavian Arterial Injuries Using Data from the AAST PROOVIT Registry - Guntur, Grahya; DuBose, Joseph J; Bee, Tiffany K; Fabian, Timothy; Morrison, Jonathan; Skarupa, David J; Inaba, Kenji; Kundi, Rishi; Scalea, Thomas; Feliciano, David V (Journal of Endovascular Resuscitation and Trauma Management, 2021)
Background: Endovascular repair has emerged as a viable repair option for axillo-subclavian arterial injuries in select patients; however, further study of contemporary outcomes is warranted. Methods: The American Association for the Surgery of Trauma (AAST) PROspective Observational Vascular Injury Treatment (PROOVIT) registry was used to identify patients with axillo-subclavian arterial injuries from 2013 to 2019. Demographics and outcomes were compared between patients undergoing endovascular repair versus open repair. Results: 167 patients were identified, with intervention required in 107 (64.1%). Among these, 24 patients underwent open damage control surgery (primary amputation = 3, ligation = 17, temporary vascular shunt = 4). The remaining 83 patients (91.6% male; mean age 26.0 ± 16) underwent either endovascular repair (36, 43.4%) or open repair (47, 56.6%). Patients managed with definitive endovascular or open repair had similar demographics and presentation, with the only exception being that endovascular repair was more commonly employed for traumatic pseudoaneurysms (p = 0.004). Endovascular repair was associated with lower 24-hour transfusion requirements (p = 0.012), but otherwise the two groups were similar with regards to in-hospital outcomes. Conclusion: Endovascular repair is now employed in > 40% of axillo-subclavian arterial injuries undergoing repair at initial operation and is associated with lower 24-hour transfusion requirements, but otherwise outcomes are comparable to open repair.